Blue Copper Peroxidase and Phthalocyanine Conjugate: Synthesis, Characterization, and Applications - Goksel, Meltem (Amer Chemical Soc, 2019)
Trametes versicolor can degrade bark as a source for carbon necessity. Therefore, it secretes lignin peroxidase, mangan peroxidase, and laccase. The laccase enzyme was produced in high yield at pH of 5 and glucose concentration of 10 g L-1. In optimized medium, the enzyme activity was between 200 and 250 U L-1 when an inducer was absent. It was seen that the activity reached 400 U L-1 when phenol was used as an inducer. The molecular weight of purified laccase was found to be 80 kDa with SDS-PAGE, and kinetic constant K-m and V-max values for 2,2'-azino-bis(3-ethylbenzthiazoline)-6-sulfonate were determined to be 3.66 x 10(-4) mu M and 1652 U L-1, respectively. Because of these properties, these enzymes are widely used, free or immobilized, in industrial areas. Laccase enzyme decolorization of six different dyes was carried out. A decolorization capacity of 50-99% was achieved by cultivation for 20 days using a beginning dye concentration of 20 ppm. The removal of color with an active enzyme was obtained around 90%. Also, the laccase enzyme was conjugated, amine-functionalized, low-symmetry phthalocyanine. This conjugate was examined by both photodynamic therapy and chemosensor application. This conjugate fluorescence had a quantum yield of 0.32 (lifetime 3.59 ns) and efficiently generated singlet oxygen (quantum yield 0.4). The conjugate successfully displayed photodamage in HeLa and HuH-7 cells in the photodynamic therapy application. These results indicate that the conjugate represents an interesting agent with potential applications in photodynamic therapy. In addition, the chemosensor behavior of this compound to different metal ions has been studied, and this conjugate is displayed as a fluorescence chemosensor for the determination of Fe3+ ions.
Keywords: Trametes-Versicolor; Phanerochaete-Chrysosporium; Photochemical Properties; Laccase; Chemosensor; Decolorization; Substituents; Enzyme; Fe3+